Case report: Indolent drug-related pneumonitis with alectinib therapy in the treatment of non-small cell lung cancer - Chen, Xianmeng; Xia, Daqing; Jiang, Xuqin; Cao, Lejie; Ryu, Jay H.; Hu, Xiaowen (Frontiers in Pharmacology, 2022)
Molecular targeting therapy is becoming the standard of care for some patients with anaplastic lymphoma kinase (ALK)-rearranged lung adenocarcinoma. Drug-related pneumonitis (DRP) has been identified as an infrequent but potentially severe adverse effect. Herein, we report a 50-year-old woman with ALK-rearranged advanced lung adenocarcinoma who developed interstitial lung disease (ILD) associated with alectinib therapy. At 102-days of treatment, chest CT revealed scattered ground glass opacities (GGOs) involving both lungs. Since she was asymptomatic and alectinib provided a beneficial tumor treatment response, alectinib therapy was continued. However, two months later, she presented with progressive dyspnea and diffuse GGOs on chest CT. There was no evidence for infection or other etiologies for her lung complication. Alectinib was discontinued and steroid therapy was initiated which was followed by improvement in respiratory symptoms and chest CT findings; DRP was diagnosed. Although rare, alectinib therapy can cause DRP of indolent onset.